Prospective Study of BMI and the Risk of Pulmonary Embolism in Women - Kabrhel, Christopher (2009)
Pulmonary embolism (PE) is common and associated with significant morbidity and mortality. An association between obesity and PE has been suggested, but the nature of the association has not been well defined. We performed a prospective cohort study of 87,226 women in the Nurses’ Health Study (1984–2002) to define the association between BMI and the risk of incident PE. Primary exposure was BMI (<22.5, 22.5–24.9, 25.0–27.4, 27.5–29.9, 30.0–34.9, and ≥35.0 kg/m(2)). Primary outcome was idiopathic PE (medical record confirmed cases of PE not associated with prior surgery, trauma, or malignancy). Secondary analysis of nonidiopathic PE was also performed. Multivariable Cox proportional hazards models were controlled for age, physical activity, caloric intake, smoking, pack-years, race, spouse’s educational attainment, parity, menopause, nonaspirin nonsteroidal anti-inflammatory drugs, warfarin, multivitamin supplements, hypertension, coronary heart disease, and rheumatological disease. There were 157 incident idiopathic PE and 338 nonidiopathic PE. There was a strong positive association between BMI, the risk of idiopathic PE (relative risk (RR) = 1.08 (95% confidence interval (CI), 1.06–1.10) per 1 kg/m(2) increase in BMI, P < 0.001) and nonidiopathic PE (RR = 1.08 (95% CI, 1.07–1.10), P < 0.001). The association was linear, and apparent even with modest increases in BMI (22.5–25 kg/m(2)). The risk increased nearly sixfold among subjects with BMI ≥35 kg/m(2), and was present in multiple subgroups. Increasing BMI has a strong, linear association with the development of PE in women. Clinicians should consider BMI when assessing the risk of PE in their patients.